2016
DOI: 10.1021/acs.jpcb.5b12375
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Thermodynamics of Hydrogen Bonding in Alcohol-Containing Mixtures: Cross-Association

Abstract: The thermodynamics of hydrogen bonding in 1-alcohol + water binary mixtures is studied using molecular dynamic (MD) simulation and the polar and perturbed chain form of the statistical associating fluid theory (polar PC-SAFT). The fraction of free monomers in pure saturated liquid water is computed using both TIP4P/2005 and iAMOEBA simulation water models. Results are compared to spectroscopic data available in the literature as well as to polar PC-SAFT. Polar PC-SAFT models hydrogen bonds using single bondabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 109 publications
(151 reference statements)
9
81
0
Order By: Relevance
“…In Fig. 4 we compare TPT1 and TPT2 predictions to MD simulations (same reference 28 and methodology as Fig. 3 for ethanol, with water modeled with the i-AMOEBA 43 The MD calculation of ( ) in Fig.…”
Section: B Predictions Of Ethanol-water Hydrogen Bondingmentioning
confidence: 99%
See 3 more Smart Citations
“…In Fig. 4 we compare TPT1 and TPT2 predictions to MD simulations (same reference 28 and methodology as Fig. 3 for ethanol, with water modeled with the i-AMOEBA 43 The MD calculation of ( ) in Fig.…”
Section: B Predictions Of Ethanol-water Hydrogen Bondingmentioning
confidence: 99%
“…26 There has been much debate in the literature on whether alcohols should be modeled with two (one donor and one acceptor in a 2B scheme) or three association sites. 27,28 Recently, Fouad et al 28 demonstrated that within the polar PC-SAFT equation of state, the 2B scheme gave better agreement with hydrogen bonding distributions in pure alcohols. However, it was simultaneously shown that the 3C model gave better agreement for hydrogen bonding distributions for alcohol-water mixtures, as well as well as improved phase behavior predictions with water.…”
Section: I: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact interpretation of Luck's data is difficult. Application of TPT to water has met with mixed results 7,15,16,23,28,29 in the description of Lucks data. It has been shown 16,28 that…”
mentioning
confidence: 99%